Supersonic flow analysis and evaluation of damping derivative - Monis, Renita Sharon; Shabana, Ayesha; Crasta, Asha; Khan, Sher Afghan (International Organization of Scientific Research ( IOSR ), 2016)
The emphasis of this paper is to examine the variation of damping derivative with incidence angle and Mach number with varying pivot position. The damping derivative decreases with Mach number and increases with the incidence angle. It is also seen that for a given Mach number the damping derivatives are decreasing and reaches a minimum value and then again increases and attains the same value which was at h = 0, for pivot position h = 0 to h = 1.0 and at h = 0.5 it attains a minimum value and then increases for h = 0.6 to h = 1. The Damping derivative decreases with Mach number for the varying pivot position.